The PDEM-based time-varying dynamic reliability analysis method for a concrete dam subjected to earthquake. (October 2021) - Chen, Jianyun; Jia, Qibin; Xu, Qiang; Fan, Shuli; Liu, Pengfei
Abstract: A time-varying dynamic reliability analysis method based on the generalized probability density evolution method (GPDEM) is proposed for a concrete gravity dam under seismic loading. Characterized by considering both randomness and time-variability, the method could be applied to predict the time-varying seismic performance of concrete dams from the perspective of probability. Two probability density evolution equations (PDEEs) are established in the method: the extreme value distribution-based PDEE.1 considering the randomness of material parameters under seismic loading and the PDEE.2 considering the deterioration of material properties during the service life. To solve the PDEE.2, a novel initial condition is derived from the PDEE.1 for the first time. The numerical implementation is illustrated by a concrete gravity dam. The results show that the abundant and continuous probability evolution information of the time-varying seismic performance could be captured. Then, the continuous time-varying reliabilities are obtained through the specified thresholds. The accuracy and effectiveness of the newly proposed method are compared with those of the MCS. Finally, the proposed method is verified to be efficient and be suitable for complex nonlinear structures under seismic loading, which could provide a potential tool for the life-cycle seismic design.